calculus-derivatives

posted by .

y=cos^3(12theta)

find derivative using chain rule

• calculus-derivatives -

y = x^3

x = cos(z)

z = 12 teta

dy/dtheta =

(dy/dz) (dz/dtheta) =

(dy/dx) (dx/dz) (dz/dtheta) =

3 x^2 [-sin(z)] 12 =

-36 cos^2(z) sin(z) =

-36 cos^2(12 theta) sin(12 theta)

Similar Questions

1. Math - Calculus Question.

hey can someone explain to me the relationship between the chain rule and implicit differentiation?

Also can I get some help with this LONG, TIRESOME PROBLEM?
3. Calculus/Derivatives

In addition, can you walk me through how to get the derivatives for these 2 statements, too?
4. Calculus

How do I use the chain rule to find the derivative of square root(1-x^2) also, are there any general hints or tips for determining when the chain rule and product or quotient rule should be used?
5. calculus

Please help. Applying the chain rule, how do I find the derivative of f(x)=In(e^x-e^-x) (x>0) and then using this answer use the quotient rule to find the second derivative. I cannot do this so any answer greatly appreciated.
6. Calculus

Find the derivative of f(x) =cos^-1(x^2) Ok so I'm having a little confusion with the chain rule and I'm not sure if my answer is right... will the answer be... 2x(-cos^-2(x^2)(-sin(x^2)?
7. Calculus

Find the outside and inside functions of the following to find their derivatives: 1) sqrt(2x+9) 2) cos(cos(x)) 3) tan(x) I already know how to find their derivatives I'm just not exactly sure what parts of the chain rule equation would …
8. Derivatives

Find the derivatives of: 1. H(x)= sin2xcos2x The answer given is 2cos4x. My question is, how in the world did they get that!?
9. Calculus

Find f'(x) if f(x)=sin^3(4x) A. 4cos^3(4x) B. 3sin^2(4x)cos(4x) C. cos^3(4x) D. 12sin^2(4x)cos(4x) E. None of these I got D using the chain rule?
10. Calculus

Just got through with derivatives, power rule, and chain rule. I am supposed to find the first and second derivatives of the function. y = 4x/√x+1 and y = cos^2(x) y' = [(x+1)^(1/2)(4)]-[(4x)(1/2(x+1)^(-1/2))(1)] y' = [4(x+1)^(1/2)-4x]/[2(x+1)^(1/2)(x+1)] …

More Similar Questions